2014
DOI: 10.1126/science.1251688
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of Mexico recapitulates Native American substructure and affects biomedical traits

Abstract: Mexico harbors great cultural and ethnic diversity, yet fine-scale patterns of human genome-wide variation from this region remain largely uncharacterized. We studied genomic variation within Mexico from over 1,000 individuals representing 20 indigenous and 11 mestizo populations. We found striking genetic stratification among indigenous populations within Mexico at varying degrees of geographic isolation. Some groups were as differentiated as Europeans are from East Asians. Pre-Columbian genetic substructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
423
6
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 430 publications
(502 citation statements)
references
References 63 publications
(43 reference statements)
52
423
6
11
Order By: Relevance
“…The Mexican population also harbors great ethnic diversity [108] as confirmed by numerous studies on the admixture in Mexico. Amerindian ancestry is the largest component (0.51-0.56) in the general population, followed by European (0.40-0.45), while the African component is small (0.02-0.05).…”
Section: The Relationship Of Brca1/2 Mutations and Other Bc Susceptibmentioning
confidence: 82%
“…The Mexican population also harbors great ethnic diversity [108] as confirmed by numerous studies on the admixture in Mexico. Amerindian ancestry is the largest component (0.51-0.56) in the general population, followed by European (0.40-0.45), while the African component is small (0.02-0.05).…”
Section: The Relationship Of Brca1/2 Mutations and Other Bc Susceptibmentioning
confidence: 82%
“…A simple explanation for this observation was that of a genetic continuity between local pre-and post-Columbian populations (i.e., that the native population could have become amalgamated into the growing admixed population from that region). Subsequent autosomal marker surveys [including high-density singlenucleotide polymorphism (SNP) haplotype analyses] in populations from Central and South America have consistently shown that the native ancestry of these populations relates most closely to natives living in proximity (3,61,62,106). These observations suggest that, despite an increased migration across Ibero-America in recent decades, this has not been extensive enough to erase the signature of pre-Columbian native population structure.…”
Section: Subcontinental Ancestrymentioning
confidence: 85%
“…Moreover, they are not found in GTEx except in liver, where expression levels are very low (≤ 1 TPM for each of 4 mRNA species). In addition, since the genetics of Mexico are very complicated, with region-specific sub-groups being identified (75), it is likely that the MAF of 0.17 identified in the study cohort (38) will vary significantly among different populations of Mexican origin once a larger and more thorough genetic analysis is completed.…”
Section: Resultsmentioning
confidence: 99%